Hydrophilic anti-fogging transparent coating on surface of plastic substrate and preparation method of hydrophilic anti-fogging transparent coating

By using linear acrylic copolymer and active monomer on the surface of the plastic substrate, a semi-interpenetrating polymer network is formed, which solves the problems of poor water resistance and poor transparency of the existing anti-fog coating, and achieves efficient and durable hydrophilic and anti-fog effect.

CN119752266AActive Publication Date: 2025-04-04NINGBO JEEAO CHUANGYI NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411874159.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-04
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The anti-fog coating on the surface of existing plastic substrates has poor water resistance under long-term high temperature and high humidity conditions, has a short anti-fog life, and is not ideal for transparency, which cannot meet the needs of certain special scenarios.

Method used

Linear acrylic copolymer and active monomer are combined to form a semi-interpenetrating polymer network through UV curing, which enhances the adhesion between the coating and the plastic substrate and improves the anti-fog effect.

Benefits of technology

A long-term water-resistant, high temperature and humidity-resistant and high transparency hydrophilic anti-fog coating is achieved, which significantly improves the adhesion and anti-fog performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752266A_ABST
    Figure CN119752266A_ABST
Patent Text Reader

Abstract

The invention relates to the field of coatings, and discloses a hydrophilic anti-fog transparent coating on the surface of a plastic substrate and a preparation method of the hydrophilic anti-fog transparent coating. The hydrophilic anti-fog transparent coating comprises the following raw materials: 40-80% of a linear acrylic copolymer, 0.1-2% of an active monomer, 0.05-0.2% of a photoinitiator, 0-0.5% of a defoaming agent, 0-0.5% of a leveling agent and 20-60% of a solvent. Wherein the linear acrylic copolymer is formed by copolymerizing an acrylate soft monomer, a hard monomer containing an olefinic bond and a functional monomer; the functional monomer contains an olefinic bond and a hydrophilic group; the active monomer is one or more of ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate and butanediol diacrylate. The hydrophilic anti-fog coating disclosed by the invention not only has an excellent anti-fog effect, but also has good adhesive force with a plastic substrate, long-acting water resistance, high-temperature and high-humidity resistance and high transparency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, and in particular to a hydrophilic anti-fog transparent coating on the surface of a plastic substrate and a preparation method thereof. Background Art

[0002] Coatings are widely used in the construction, machinery, electronics, security and other industries. After the coating is cured, the coating mainly protects and decorates the attached objects. With the progress of the times, the market's performance requirements for coatings are gradually increasing, such as light aging resistance, high and low temperature resistance, solvent resistance, moisture resistance, scratch resistance, etc. As a result, functional coatings in the market segment have emerged, such as hardening, anti-corrosion, anti-fouling, anti-fog, fireproof, heat insulation and other coatings, and the demand is becoming stronger.

[0003] Fogging is a natural phenomenon. When the temperature and humidity of the environment change, water vapor in the air condenses on the solid surface to form small water droplets, which refracts light and affects the light transmission, causing whitening or even condensation, which brings inconvenience to production and life, and even poses a safety hazard. For example, fogging of camera lenses will cause the imaging system to fail; fogging of car windshields will affect the driver's normal driving.

[0004] To prevent fogging, a layer of hydrophilic coating is applied on the surface of the substrate to make the static contact angle of water droplets less than 30°, making it difficult for water vapor to condense into small droplets. Instead, it spreads evenly on the coating surface to form a uniform water film, which can significantly reduce the problem of decreased transmittance caused by light refraction, thus achieving an anti-fog effect.

[0005] However, due to the limitation of preparation process, the anti-fog coating on the surface of plastic substrate (such as PC substrate) generally has the problem of poor water resistance. Under long-term high temperature and high humidity conditions and soaking in water, the anti-fog life is short and has no practical value. At the same time, for some coatings with good anti-fog effect, the transparency is not ideal and cannot meet the needs of special scenes such as cameras. Therefore, it is of positive significance to develop a hydrophilic anti-fog coating that is long-lasting, water-resistant, resistant to high temperature and humidity, and highly transparent. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a hydrophilic anti-fog transparent coating on the surface of a plastic substrate and a preparation method thereof. The hydrophilic anti-fog coating of the present invention not only has an excellent anti-fog effect, but also has good adhesion to the plastic substrate, and has long-term water resistance, high temperature and high humidity resistance, and high transparency.

[0007] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a hydrophilic anti-fog transparent coating on the surface of a plastic substrate, which comprises the following raw materials in percentage by mass: 40-80% linear acrylic copolymer, 0.1-2% active monomer, 0.05-0.2% photoinitiator, 0-0.5% defoamer, 0-0.5% leveling agent, and 20-60% solvent.

[0008] The linear acrylic copolymer is copolymerized by acrylic acid ester soft monomer, olefinic hard monomer and functional monomer in the mass ratio of (20-40%): (50-70%): (1-8%); the functional monomer contains olefinic bonds and hydrophilic groups. The active monomer is one or more of ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate and butanediol diacrylate.

[0009] The hydrophilic anti-fog coating of the present invention uses a linear acrylic copolymer as the main film-forming substance. The linear acrylic copolymer is obtained by copolymerizing a specific ratio of an acrylic ester soft monomer, an olefinic hard monomer and a functional monomer. Since the molecular chain contains a hydrophilic functional monomer, it is a linear thermoplastic hydrophilic polymer and has a good anti-fog effect as a coating film-forming substance. However, the present invention finds that the linear acrylic copolymer has poor adhesion to the plastic substrate after curing and film formation, and has a poor anti-fog effect in a high temperature and high humidity or water-immersed environment. For this reason, the present invention compounded the linear acrylic copolymer with an active monomer when preparing the coating. Before the coating is cured, the active monomer is uniformly dispersed in the linear acrylic copolymer. After UV curing, a cross-linking reaction occurs between the active monomers, thereby forming a semi-interpenetrating polymer network (SIPN) with the linear acrylic copolymer. Figure 1 As shown), this can significantly enhance the adhesion between the coating and the plastic substrate, and at the same time greatly improve the anti-fog effect of the coating in high temperature and high humidity or water-immersed environments.

[0010] Furthermore, the present invention also found that the content of active monomers has an important influence on the performance of the coating: at a certain active monomer content, as the amount of active monomer increases, the adhesion of the coating gradually increases, indicating that after increasing the active monomer, the crosslinking density of the coating increases, the cohesion is enhanced, the bonding ability of the coating with the PC substrate is improved, and the anti-fog performance after high temperature, high humidity and water resistance is improved. However, when the active monomer content reaches a certain level, if its content continues to increase, the anti-fog level begins to decline, because the crosslinking density continues to increase, which will cause the hydrophilicity of the coating to decrease, affecting the anti-fog effect.

[0011] Preferably, the plastic substrate is a PC substrate, a PET substrate or a PMMA substrate.

[0012] Preferably, the acrylic acid ester soft monomer is one or more of ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate and n-octyl methacrylate.

[0013] Preferably, the hard monomer is one or more of styrene, methyl methacrylate, acrylonitrile and ethyl methacrylate.

[0014] Preferably, the functional monomer is one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, acrylamide, N-hydroxymethyl acrylamide, N,N-dimethylacrylamide, glycidyl methacrylate and vinyl pyrrolidone.

[0015] Preferably, the photoinitiator is one or more of 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, 2-isopropylthioxanthone and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0016] Preferably, the solvent is one or more of ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, isopropanol and n-butanol.

[0017] Preferably, the defoaming agent is one or more of BYK066N, BYK028 and Tego901.

[0018] Preferably, the leveling agent is one or more of BYK333, BYK375 and Tego410.

[0019] Preferably, the preparation method of the linear acrylic copolymer comprises: S1: Mixing the initiator with the acrylic ester soft monomer, the hard monomer and the functional monomer to obtain a premix.

[0020] S2: Add solvent into the reaction kettle, heat and stir.

[0021] S3: Add the premix to the solvent.

[0022] S4: Cooling after heat preservation and reaction.

[0023] Preferably, in S2, the amount of the solvent used is 105-110 wt% of the total amount of the monomers, and the heating temperature is 70-75°C.

[0024] Preferably, in S3, the premix is ​​added within 2-3 hours.

[0025] Preferably, in S4, the insulation reaction time is 2.5-3.5h.

[0026] Preferably, in S1: the initiator is one or more of dibenzoyl peroxide, azobisisobutyronitrile, ammonium persulfate, tert-butyl hydroperoxide and dicyclohexyl percarbonate; in S2: the solvent is one or more of isopropanol, isobutanol and methanol.

[0027] Preferably, the coating has an adhesion level of 0, an anti-fog level ≤3, an anti-fog level after high temperature and high humidity aging ≤3, an anti-fog level after water resistance test ≤3, and a transmittance ≥88%.

[0028] In a second aspect, the present invention provides a method for preparing the hydrophilic anti-fog transparent coating on the surface of the above-mentioned plastic substrate, which specifically comprises the following steps: 1) adding a linear acrylic copolymer, a solvent, an active monomer, a photoinitiator, a defoamer and a leveling agent into a reaction kettle and stirring the mixture to obtain a hydrophilic antifogging transparent coating.

[0029] 2) Spraying the hydrophilic anti-fog transparent coating onto the surface of the plastic substrate.

[0030] 3) One-time heating and curing.

[0031] 4) Spray the hydrophilic anti-fog transparent coating again.

[0032] 5) Heat again to cure.

[0033] 6) UV curing.

[0034] After heating and UV curing, a semi-interpenetrating polymer network structure is formed in the coating ( Figure 1 As shown). Among them, heating and curing can promote the penetration of the coating into the PC substrate, help to form a bonding layer, and UV curing improves the cohesion of the coating. In addition, the present invention finds that during the curing process after spraying, the coating surface is cured first, and the solvent in the bottom layer of the coating migrates to the surface, generating Bénard vortices, which affects the microscopic flatness of the coating and further affects the transparency of the coating. If the "one-time spraying + one-time heating and curing" process is adopted, the wet film thickness of the single-pass coating is thick and Bénard vortices are easily generated; while the "secondary spraying + secondary heating and curing" process of the present invention is adopted, the wet film thickness of the single-pass coating is thin, which can reduce the generation of Bénard vortices, so the final coating has higher transparency.

[0035] Preferably, in step 1), the stirring is performed at 600-800 rpm for 20-40 min.

[0036] Preferably, in step 2), the plastic substrate is pre-cleaned until the surface is free of water and oil.

[0037] Preferably, in steps 2) and 4), a 1.0-1.5 mm caliber spray gun, a spray pressure of 0.4-0.6 MPa, a plastic substrate transmission speed of 15-25 mm / s, and a spray gun movement speed of 0.5-1.5 m / s are used for the first spraying; a 1.0-1.5 mm caliber spray gun, a spray pressure of 0.2-0.3 MPa, a plastic substrate transmission speed of 15-25 mm / s, and a spray gun movement speed of 0.5-1.5 m / s are used for the second spraying.

[0038] Preferably, in steps 3) and 5), the temperature of the first heating and curing is 40-60°C for 5-10 min; the temperature of the second heating and curing is 70-80°C for 5-10 min.

[0039] In order to further improve the transparency of the coating, the present invention adopts the "secondary spraying + secondary heating and curing" process with the above-mentioned differentiated parameters. Specifically: during the first spraying, the spray pressure is 0.4-0.6MPa. The higher the pressure, the smaller the spray flow rate, and the thinner the coating film thickness. With the curing conditions of 40-60°C, the solvent can be evaporated quickly and quickly; during the second spraying, the spray pressure is 0.2-0.3MPa. At this time, the lower the pressure, the larger the spray flow rate, and the thicker the coating film thickness. With the curing conditions of 70-80°C, it can be quickly heated and cured together with the first sprayed coating to achieve a good leveling effect and a higher transparency of the coating.

[0040] Preferably, in step 6), the energy of the UV curing mercury lamp is 3000-5000 mJ / cm 2 , curing time <5s.

[0041] Compared with the prior art, the beneficial effects of the present invention are: (1) The hydrophilic anti-fog transparent coating of the present invention uses a linear acrylic copolymer as the main film-forming substance, which is obtained by copolymerizing a specific ratio of an acrylic ester soft monomer, an olefin-containing hard monomer, and a functional monomer. The functional monomer is hydrophilic, so the linear acrylic copolymer has a good anti-fog effect after film formation. On this basis, the present invention compounded the linear acrylic copolymer with an active monomer, and the active monomer was evenly dispersed in the linear acrylic copolymer. After UV curing, the active monomers were cross-linked to form a semi-interpenetrating polymer network with the linear acrylic copolymer, which can significantly enhance the adhesion between the coating and the plastic substrate, and at the same time greatly improve the anti-fog effect of the coating in a high temperature and high humidity or water soaking environment.

[0042] (2) The hydrophilic anti-fog transparent coating of the present invention on the PC substrate still maintains the anti-fog effect after being exposed to high temperature and high humidity (85°C / 85% relative humidity for 720 hours) and soaked in water (40°C for 240 hours). It can be used for the surface of plastic substrates that frequently work in high humidity or soaked in water, such as PC ball covers for security cameras.

[0043] (3) The present invention adopts the "secondary spraying + secondary curing" process to construct a hydrophilic anti-fog transparent coating with high transparency on the surface of the plastic substrate; further, if the "secondary spraying + secondary curing" process with differentiated parameters of the present invention is adopted, the transparency of the coating is better. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 Schematic diagram of the curing principle of the coating of the present invention; wherein: a represents a linear acrylic copolymer; b represents the addition of active monomers to the linear acrylic copolymer after the coating is compounded; c represents that after curing, the active monomers form a cross-linked polymer to form a semi-interpenetrating polymer network with the linear acrylic copolymer. DETAILED DESCRIPTION

[0045] The present invention will be further described below in conjunction with the embodiments.

[0046] Overall embodiment A hydrophilic anti-fog transparent coating on the surface of a plastic substrate comprises the following raw materials in percentage by mass: 40-80% of a linear acrylic copolymer, 0.1-2% of an active monomer, 0.05-0.2% of a photoinitiator, 0-0.5% of a defoamer, 0-0.5% of a leveling agent, and 20-60% of a solvent.

[0047] The linear acrylic copolymer is copolymerized by acrylic acid ester soft monomer, olefinic hard monomer and functional monomer in the mass ratio of (20-40%): (50-70%): (1-8%); the functional monomer contains olefinic bonds and hydrophilic groups. The active monomer is one or more of ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate and butanediol diacrylate.

[0048] In some preferred implementation cases, the plastic substrate is a PC substrate, a PET substrate or a PMMA substrate.

[0049] In some preferred implementation cases, the acrylic ester soft monomer is one or more of ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate and n-octyl methacrylate.

[0050] In some preferred implementation cases, the hard monomer is one or more of styrene, methyl methacrylate, acrylonitrile and ethyl methacrylate.

[0051] In some preferred implementation cases, the functional monomer is one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, acrylamide, N-hydroxymethyl acrylamide, N,N-dimethylacrylamide, glycidyl methacrylate and vinyl pyrrolidone.

[0052] In some preferred implementation cases, the photoinitiator is one or more of 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, 2-isopropylthioxanthone and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide.

[0053] In some preferred implementation cases, the solvent is one or more of ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, isopropanol and n-butanol.

[0054] In some preferred implementation cases, the defoaming agent is one or more of BYK066N, BYK028 and Tego901.

[0055] In some preferred implementation cases, the leveling agent is one or more of BYK333, BYK375 and Tego410.

[0056] In some preferred implementation cases, the preparation method of the linear acrylic copolymer comprises: S1: Mixing the initiator with the acrylic ester soft monomer, the hard monomer and the functional monomer to obtain a premix.

[0057] In some preferred implementation cases, in S1: the initiator is one or more of dibenzoyl peroxide, azobisisobutyronitrile, ammonium persulfate, tert-butyl hydroperoxide and dicyclohexyl percarbonate.

[0058] S2: Add solvent into the reaction kettle, heat and stir.

[0059] In some more specific implementation cases, in S2, the amount of the solvent used is 105-110 wt% of the total amount of the monomers, and the heating temperature is 70-75°C.

[0060] In some more preferred implementation cases, in S2: the solvent is one or more of isopropanol, isobutanol and methanol.

[0061] S3: Add the premix to the solvent.

[0062] In some more specific implementation cases, in S3, the premix is ​​added within 2-3 hours.

[0063] S4: Cooling after heat preservation and reaction.

[0064] In some more specific implementation cases, in S4, the insulation reaction time is 2.5-3.5 hours.

[0065] In some preferred implementation cases, the coating has an adhesion level = 0, an anti-fog level ≤ 3, an anti-fog level after high temperature and high humidity aging ≤ 3, an anti-fog level after water resistance test ≤ 3, and a transmittance ≥ 88%.

[0066] A method for preparing the above-mentioned hydrophilic anti-fog transparent coating on the surface of the plastic substrate specifically comprises the following steps: 1) adding a linear acrylic copolymer, a solvent, an active monomer, a photoinitiator, a defoamer and a leveling agent into a reaction kettle and stirring the mixture to obtain a hydrophilic antifogging transparent coating.

[0067] In some more specific implementation cases, in step 1), the stirring is performed at 600-800 rpm for 20-40 min.

[0068] 2) Spraying the hydrophilic anti-fog transparent coating onto the surface of the plastic substrate.

[0069] In some more specific implementation cases, in step 2), the plastic substrate is pre-cleaned until the surface is free of water and oil.

[0070] In some more specific implementation cases, in step 2), the hydrophilic anti-fog transparent coating is sprayed with a 1.0-1.5 mm caliber spray gun, the spray pressure is 0.4-0.6 MPa, the plastic substrate transmission speed is 15-25 mm / s, and the spray gun movement speed is 0.5-1.5 m / s.

[0071] 3) One-time heating and curing.

[0072] In some more specific implementation cases, in step 3), the temperature of the primary heating curing is 40-60° C., and the time is 5-10 min.

[0073] 4) Spray the hydrophilic anti-fog transparent coating again.

[0074] In some more specific implementation cases, in step 4), the hydrophilic anti-fog transparent coating is sprayed with a 1.0-1.5 mm caliber spray gun, the spray pressure is 0.2-0.3 MPa, the plastic substrate transmission speed is 15-25 mm / s, and the spray gun movement speed is 0.5-1.5 m / s.

[0075] 5) Heat again to cure.

[0076] In some more specific implementation cases, in step 3), the temperature of the reheating and curing is 70-80° C. and the time is 5-10 min.

[0077] 6) UV curing.

[0078] In some more specific implementation cases, in step 6), the energy of the mercury lamp is 3000-5000 mJ / cm 2 , curing time <5 seconds.

[0079] Specific Examples and Comparative Examples The coating performance test method is as follows: Anti-fog level comparison table Grade / Level Judgment basis 1 Uniform water film, completely transparent, no water droplets 2 The local uneven water film with an area below 5% has good transparency and a small amount of water droplets are formed. 3 The local uneven water film below 30% of the area has more water droplets formed. 4 Uneven water film over 30% area. (I) Effect of different active monomer dosages S1: Take 300g of acrylic acid ester soft monomer (isooctyl acrylate), 650g of hard monomer (methyl methacrylate), 50g of functional monomer (N,N-dimethylacrylamide), and 3g of initiator (dibenzoyl peroxide), and mix them to obtain a premix; take 1050g of solvent 1 (isobutyl alcohol) and add it into a reactor, and stir and reflux under water bath heating to 72°C; after the temperature stabilizes, add the premix into the reactor at a uniform speed through a peristaltic pump within 2.5h, keep it warm for 3h, and then cool it to room temperature to obtain a linear acrylic copolymer.

[0080] S2: Add 600 g of linear acrylic copolymer, active monomer (polyethylene glycol diacrylate, Average Mn750) (added amount see Table 1), 0.5 g of photoinitiator (2,4,6 (trimethylbenzoyl) diphenylphosphine oxide), 1 g of defoamer (BYK028), 2 g of leveling agent (BKY333) and solvent di(propylene glycol methyl ether) (to a total amount of 1000 g) into another reaction kettle, and disperse at 700 rpm for 30 min to obtain a hydrophilic anti-fog transparent coating.

[0081] S3: Clean the PC substrate until the surface is free of water and oil, transfer the plastic substrate through a conveyor belt, set a spray gun that reciprocates horizontally (perpendicular to the conveying direction) above the conveyor belt, and spray the hydrophilic anti-fog transparent coating with a 1.2mm caliber spray gun, wherein: the spray pressure is 0.5MPa, the plastic substrate transmission speed is 20mm / s, and the spray gun movement speed is 1m / s; bake in a 55℃ oven for 8min to form a coating with a thickness of about 4μm.

[0082] S4: Spray the hydrophilic anti-fog transparent coating again with a 1.2 mm diameter spray gun, where: the spray pressure is 0.3 MPa, the plastic substrate transmission speed is 20 mm / s, and the spray gun movement speed is 1 m / s; bake in a 75 °C oven for 8 min; and finally heat at an energy of 4000 mJ / cm 2 The film was cured under a mercury lamp for 4 seconds to form a coating with a total thickness of about 12 microns.

[0083] The performance test results of the obtained coating are shown in Table 1: Table 1 From the comparison of the data in the above table, we can see that: (1) The test results show that from Comparative Example 1, Example 1 to Example 2, as the amount of active monomer increases, the adhesion of the coating increases from level 2 to level 0, indicating that after adding the active monomer, the crosslinking density of the coating increases, the cohesive force is enhanced, and the bonding ability of the coating with the PC substrate is improved. At the same time, the anti-fog performance after high temperature and high humidity resistance and water resistance is improved accordingly, and the best state is reached at the addition amount of Example 2 (1%).

[0084] (2) The test results show that from Example 2, Example 3 to Comparative Example 2, the amount of active monomer continued to increase, and the anti-fog level began to decrease, indicating that further increasing the cross-linking density will lead to a decrease in the hydrophilicity of the coating and affect the anti-fog effect.

[0085] 2. Influence of different types of active monomers S1: Take 300g of acrylic acid ester soft monomer (isooctyl acrylate), 650g of hard monomer (methyl methacrylate), 50g of functional monomer (N,N-dimethylacrylamide), and 3g of initiator (dibenzoyl peroxide), and mix them to obtain a premix; take 1050g of solvent 1 (isobutyl alcohol) and add it into a reactor, and stir and reflux under water bath heating to 72°C; after the temperature stabilizes, add the premix into the reactor at a uniform speed through a peristaltic pump within 2.5h, keep it warm for 3h, and then cool it to room temperature to obtain a linear acrylic copolymer.

[0086] S2: Add 600 g of linear acrylic copolymer, 10 g of active monomer (types see Table 2), 0.5 g of photoinitiator (2,4,6 (trimethylbenzoyl) diphenylphosphine oxide), 1 g of defoamer (BYK028), 2 g of leveling agent (BKY333) and solvent di(propylene glycol methyl ether) (to a total amount of 1000 g) into another reaction kettle, and disperse at 700 rpm for 30 min to obtain a hydrophilic anti-fog transparent coating.

[0087] S3: Clean the PC substrate until the surface is free of water and oil, transfer the plastic substrate through a conveyor belt, set a spray gun that reciprocates horizontally (perpendicular to the conveying direction) above the conveyor belt, and spray the hydrophilic anti-fog transparent coating with a 1.2mm caliber spray gun, wherein: the spray pressure is 0.5MPa, the plastic substrate transmission speed is 20mm / s, and the spray gun movement speed is 1m / s; bake in a 55℃ oven for 8min to form a coating with a thickness of about 4μm.

[0088] S4: Spray the hydrophilic anti-fog transparent coating again with a 1.2 mm diameter spray gun, where: the spray pressure is 0.3 MPa, the plastic substrate transmission speed is 20 mm / s, and the spray gun movement speed is 1 m / s; bake in a 75 °C oven for 8 min; and finally heat at an energy of 4000 mJ / cm 2 The film was cured under a mercury lamp for 4 seconds to form a coating with a total thickness of about 12 microns.

[0089] The performance test results of the obtained coating are shown in Table 2: Table 2 From the comparison of the data in the above table, it can be seen that in Example 2, Example 4-5, as the polyether segment in the active monomer increases, the molecular weight of the monomer increases. Under the same content, as the molecular weight increases, the anti-fog effect of the coating increases from level 2 to level 1; but the water resistance and high temperature and humidity resistance of the coating will also be affected. Comprehensively considering the results of various performance indicators, the optimal average molecular weight (Average Mn) of polyethylene glycol diacrylate is 750.

[0090] (III) Effect of different spraying processes on coating transparency Comparative Example 3 (using one-time spraying and one-time heating curing process) S1: Take 300g of acrylic acid ester soft monomer (isooctyl acrylate), 650g of hard monomer (methyl methacrylate), 50g of functional monomer (N,N-dimethylacrylamide), and 3g of initiator (dibenzoyl peroxide), and mix them to obtain a premix; take 1050g of solvent 1 (isobutyl alcohol) and add it into a reactor, and stir and reflux under water bath heating to 72°C; after the temperature stabilizes, add the premix into the reactor at a uniform speed through a peristaltic pump within 2.5h, keep it warm for 3h, and then cool it to room temperature to obtain a linear acrylic copolymer.

[0091] S2: Add 600 g of linear acrylic copolymer, 10 g of active monomer (polyethylene glycol diacrylate, Average Mn750), 0.5 g of photoinitiator (2,4,6 (trimethylbenzoyl) diphenylphosphine oxide), 1 g of defoamer (BYK028), 2 g of leveling agent (BKY333) and solvent di(propylene glycol methyl ether) (to a total amount of 1000 g) into another reaction kettle, and disperse at 700 rpm for 30 min to obtain a hydrophilic anti-fog transparent coating.

[0092] S3: Clean the PC substrate until the surface is free of water and oil, transfer the plastic substrate through a conveyor belt, set a spray gun with horizontal reciprocating motion (perpendicular to the conveying direction) above the conveyor belt, and spray the hydrophilic anti-fog transparent coating with a 1.2mm caliber spray gun, where: the spray pressure is 0.2MPa, the plastic substrate transmission speed is 15mm / s, and the spray gun movement speed is 1m / s; bake in a 75℃ oven for 16min, and finally heat at an energy of 4000mJ / cm 2 The film was cured under a mercury lamp for 4 seconds to form a coating with a total thickness of about 12 microns.

[0093] Example 6 (parameters of secondary spraying and heating curing are opposite to those of Example 1) S1: Take 300g of acrylic acid ester soft monomer (isooctyl acrylate), 650g of hard monomer (methyl methacrylate), 50g of functional monomer (N,N-dimethylacrylamide), and 3g of initiator (dibenzoyl peroxide), and mix them to obtain a premix; take 1050g of solvent 1 (isobutyl alcohol) and add it into a reactor, and stir and reflux under water bath heating to 72°C; after the temperature stabilizes, add the premix into the reactor at a uniform speed through a peristaltic pump within 2.5h, keep it warm for 3h, and then cool it to room temperature to obtain a linear acrylic copolymer.

[0094] S2: Add 600 g of linear acrylic copolymer, 10 g of active monomer (polyethylene glycol diacrylate, Average Mn750), 0.5 g of photoinitiator (2,4,6 (trimethylbenzoyl) diphenylphosphine oxide), 1 g of defoamer (BYK028), 2 g of leveling agent (BKY333) and solvent di(propylene glycol methyl ether) (to a total amount of 1000 g) into another reaction kettle, and disperse at 700 rpm for 30 min to obtain a hydrophilic anti-fog transparent coating.

[0095] S3: Clean the PC substrate until the surface is free of water and oil, transfer the plastic substrate through a conveyor belt, set a spray gun that reciprocates horizontally (perpendicular to the conveying direction) above the conveyor belt, and spray the hydrophilic anti-fog transparent coating with a 1.2mm caliber spray gun, wherein: the spray pressure is 0.3MPa, the plastic substrate transmission speed is 20mm / s, and the spray gun movement speed is 1m / s; bake in a 75℃ oven for 8min to form a coating with a thickness of about 8 microns.

[0096] S4: Spray the hydrophilic anti-fog transparent coating again with a 1.2 mm diameter spray gun, wherein the spray pressure is 0.5 MPa, the plastic substrate transmission speed is 20 mm / s, and the spray gun movement speed is 1 m / s; bake in a 55°C oven for 8 min; and finally heat at an energy of 4000 mJ / cm 2 The film was cured under a mercury lamp for 4 seconds to form a coating with a total thickness of about 12 microns.

[0097] The performance test results of the obtained coating are shown in Table 3: Table 3 From the comparison of the data in the above table, we can see that: (1) Comparative Example 3 adopts the spraying process of "one spraying + one curing", while Example 6 and Example 2 adopt the spraying process of "one spraying + one curing + two spraying + two curing". The results show that the transmittance of the coating finally formed by Example 6 and Example 2 using the spraying process of "one spraying + one curing + two spraying + two curing" is significantly higher than that of Comparative Example 3.

[0098] (2) Furthermore, the difference between Example 2 and Example 6 is that the two spraying parameters and heating curing parameters in Example 6 are opposite to those in Example 2. The results show that the transmittance of the coating obtained by the two-step differential spraying-curing process of Example 2 is higher. The reason is that the differential spraying-curing process in Example 2 increases the spray pressure of the first spraying, while reducing the pressure of the second spraying, so that the thickness of the coating is low for the first time and high for the second spraying. With the appropriate curing temperature, the coating can achieve the effect of mirror leveling to the greatest extent while reducing the Bénard vortices during the curing process.

[0099] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0100] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A hydrophilic anti-fog transparent coating on the surface of a plastic substrate, characterized in that The following raw materials are included in the following mass percentages: Linear acrylic copolymer 40-80%, Active monomer 0.1-2%, Photoinitiator 0.05-0.2%, Defoamer 0-0.5%, Leveling agent 0-0.5%, Solvent 20-60%; The linear acrylic copolymer is copolymerized by acrylic ester soft monomer, olefinic hard monomer and functional monomer in a mass ratio of (20-40%): (50-70%): (1-8%); The functional monomer contains olefinic bonds and hydrophilic groups; The active monomer is one or more of ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate and butanediol diacrylate.

2. The coating according to claim 1, characterized in that: The plastic substrate is a PC substrate, a PET substrate or a PMMA substrate.

3. The coating according to claim 1, characterized in that: The acrylic acid ester soft monomer is one or more of ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate and n-octyl methacrylate; The hard monomer is one or more of styrene, methyl methacrylate, acrylonitrile and ethyl methacrylate; The functional monomer is one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, acrylamide, N-hydroxymethyl acrylamide, N,N-dimethyl acrylamide, glycidyl methacrylate and vinyl pyrrolidone.

4. The coating according to claim 1, characterized in that: The photoinitiator is one or more of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, 2-isopropylthioxanthone and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide; The solvent is one or more of ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, isopropanol and n-butanol; The defoaming agent is one or more of BYK066N, BYK028 and Tego901; The leveling agent is one or more of BYK333, BYK375 and Tego410.

5. The coating according to claim 1, characterized in that: Adhesion level = 0, anti-fog level ≤3, anti-fog level after high temperature and high humidity aging ≤3, anti-fog level after water resistance test ≤3, transmittance ≥88%.

6. A method for preparing a hydrophilic anti-fog transparent coating on a plastic substrate according to any one of claims 1 to 5, characterized in that include: 1) mixing a linear acrylic copolymer, a solvent, an active monomer, a photoinitiator, a defoaming agent and a leveling agent to obtain a hydrophilic anti-fog transparent coating; 2) Spraying the hydrophilic anti-fog transparent coating onto the surface of the plastic substrate; 3) One-time heating and curing; 4) Spray the hydrophilic anti-fog transparent coating again; 5) Heat again to cure; 6) UV curing.

7. The preparation method according to claim 6, characterized in that: The preparation method of the linear acrylic copolymer comprises: S1: mixing the initiator with the acrylic soft monomer, the hard monomer and the functional monomer to obtain a premix; S2: heating and stirring the solvent; S3: adding the premix to the solvent; S4: Cooling after heat preservation and reaction.

8. The preparation method according to claim 7, characterized in that: In S2, the amount of the solvent is 105-110wt% of the total amount of the monomers, and the heating temperature is 70-75°C; In S3, the premix is ​​added within 2-3 hours; In S4, the insulation reaction time is 2.5-3.5h.

9. The preparation method according to claim 7, characterized in that: The solvent is one or more of isopropanol, isobutanol and methanol; The initiator is one or more of dibenzoyl peroxide, azobisisobutyronitrile, ammonium persulfate, tert-butyl hydroperoxide and dicyclohexyl percarbonate.

10. The preparation method according to claim 6, characterized in that: In steps 2) and 4), the first spraying is performed with a 1.0-1.5 mm diameter spray gun, a spray pressure of 0.4-0.6 MPa, a plastic substrate transmission speed of 15-25 mm / s, and a spray gun movement speed of 0.5-1.5 m / s; For the second spraying, use a 1.0-1.5mm diameter spray gun, spray pressure 0.2-0.3MPa, plastic substrate transmission speed 15-25mm / s, spray gun movement speed 0.5-1.5m / s; In steps 3) and 5), the temperature of the first heating and curing is 40-60°C for 5-10 minutes; the temperature of the second heating and curing is 70-80°C for 5-10 minutes; In step 6), the energy of the UV curing mercury lamp is 3000-5000mJ / cm 2 , curing time <5s.

Citation Information

Patent Citations

  • Zwitterionic-doped hydrogels and Anti-fogging coatings comprising the same

    CA3230683A1

  • Preparation method of long-acting hydrophilic antifog light-cured resin

    CN103910835A

  • Hydrophilic antifogging coating and preparation method thereof, and protective film and preparation method thereof

    CN114836126A

  • Water-based UV (ultraviolet) curing antifogging coating as well as preparation and application methods thereof

    CN115160842A

  • Water-based anti-fog self-cleaning automotive glass coating and preparation method thereof

    CN116004071A